District census handbook: village and townwise primary census abstract (West Bengal) - West Bengal. Distrct Census handbook (Calcutta, 1991)
The District Census Handbook compiled by the Directorate of Census Operations, West Bengal on behalf of the Government of West Bengal, owes its origin to 1951 Census. The present publication of 1991 Census is fifth in the series. In this publication besides census statistics, various other information and statistical data have been included which are used by the State Government, District Administration, Research Scholars and other data users. It contains important census tables, PCA for each village and town of the district and at the same time presented in such a manner that the comparability of the data of the earlier censuses are maintained. The publication is brought out in two parts. Part XII-A related to village and town directory and Part XII-B related to village and town PCA. Besides, for the first time in this census, at the instance of the State Govt. of West Bengal, a separate combined volume on Calcutta Metropolitan Area has also been compiled. The structuring formats and additional volumes have been made with a view to assist not only in local area planning but also to meet requirement of the Revised Minimum Needs Programme. Likewise formats of the town directory have been so devised not only to meet the requirement of Revised Minimum Needs Programme but also to give an idea about the civic and other amenities in the town. The format of the Primary Census Abstract for villages and towns has been formulated in the light of changes in the economic and other questions canvassed through the individual slips of 1991 Census.
Keywords: Census Haora -1991